Documentation, analysis and redevelopmentof the Tamsui river side in Taipei City: Reactivating the Tamsui River: A Path to people-centered urbanism and environmental consciousness (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Taipei is located on the Tamsui River's right side, which has played an important role in thecity's economic, social, and urban development. During the 1960s, population growth and fasturbanization resulted in development without sufficient management of the alluvial plains. Followingsome severe flooding in the 1960s, and in order to fulfill the increased demand for building land, thegovernment devised a flood-control plan that included the construction of a 117-kilometer-long floodwallwith a height range of 6.00 to 9.50 meters. Taipei became a walled city as a result, encircled by a highwall that separates the city from the river, compromising inhabitants' affinity with water. The goal ofthe vision presented in this paper is to make a city for people, to repair the relationship between theTamsui and its peopleby increasing access and public areas on both sides of the floodwall, allowing theriver to be reintegrated into Taipei as an extension of the city. The ability to replicate this timely action ona large scale, through a reactivation-capable process of the riverfront, to mend the original connectionbetween people, Taipei, and the Tamsui river, aims to define a shift toward a people-centered urbanismand an environmentally conscious society, with the goal of becoming a source of hope and inspirationfor our cities' aspirations to build a better future.